Cardiovascular events following coronavirus disease 2019 vaccination in adults : a nationwide Swedish study - Xu, Yiyi; Li, Huiqi; Santosa, Ailiana; Wettermark, Björn; Fall, Tove; Björk, Jonas ; 0000-0003-1883-2000; Börjesson, Mats; Gisslén, Magnus; Nyberg, Fredrik (European Heart Journal, 2025)
Background and Aims. While the rationale for coronavirus disease 2019 (COVID-19) vaccination is to reduce complications and overall mortality, some cardiovascular complications from the vaccine itself have been demonstrated. Myocarditis and pericarditis are recognized as rare acute adverse events after mRNA vaccines in young males, while evidence regarding other cardiovascular events remains limited and inconsistent. This study assessed the risks of several cardiovascular and cerebrovascular events in a Swedish nationwide register-based cohort. Methods. Post-vaccination risk of myocarditis/pericarditis, dysrhythmias, heart failure, myocardial infarction, and cerebrovascular events (transient ischaemic attack and stroke) in several risk windows after each vaccine dose were assessed among all Swedish adults (n = 8 070 674). Hazard ratios (HRs) with 95% confidence intervals (95% CIs) compared with unvaccinated were estimated from Cox regression models adjusted for potential confounders. Results. For most studied outcomes, decreased risks of cardiovascular events post-vaccination were observed, especially after dose three (HRs for dose three ranging from .69 to .81), while replicating the increased risk of myocarditis and pericarditis 1–2 weeks after COVID-19 mRNA vaccination. Slightly increased risks, similar across vaccines, were observed for extrasystoles [HR 1.17 (95% CI 1.06–1.28) for dose one and HR 1.22 (95% CI 1.10–1.36) for dose two, stronger in elderly and males] but not for arrhythmias and for transient ischaemic attack [HR 1.13 (95% CI 1.05–1.23), mainly in elderly] but not for stroke. Conclusions. Risk of myopericarditis (mRNA vaccines only), extrasystoles, and transient ischaemic attack was transiently increased after COVID-19 vaccination, but full vaccination substantially reduced the risk of several more severe COVID-19-associated cardiovascular outcomes, underscoring the protective benefits of complete vaccination.
Keywords: Cardiovascular diseases; COVID-19 vaccine; Survival analysis